Studies to elucidate mechanisms underlying the anticataract effect of annatto tocotrienol in rats / Nurul Alimah Abdul Nasir - Abdul Nasir, Nurul Alimah (Institute of Graduate Studies, UiTM, 2017)
Cataract, the leading cause of blindness, is currently treated only by surgery. Cataract carries risk of complications and its management increases economic burden. Thus, development of pharmacological options with anticataract effects is important. Oxidative-nitrosative stress, non-enzymatic glycation and osmotic stress underlie cataractogenesis. Since tocotrienol possesses biological properties that may suppress pathophysiological mechanism of cataractogenesis, we investigated its anticataract effects in rats. Tocotrienol was formulated into two widely used colloidal drug delivery systems, microemulsion and liposome, due to its poor aqueous solubility. Firstly, the dose-dependent effects of microemulsion of tocotrienol on cataractogenesis were studied in galactose-fed rats to determine the most effective dose of tocotrienol. Different concentrations of tocotrienol were applied topically twice daily from three weeks prior to galactose diet and continued for four weeks along with galactose diet. Cataract progression was monitored and after euthanization, lenticular oxidative stress was measured. Subsequently, using the most effective dose, anticataract efficacy of microemulsion and liposomal formulation was compared in galactose-fed rats. Additionally, ocular tissue distribution of a lipophilic dye using these formulations was studied. For this distribution study, single drop of solution or formulation containing lipophilic dye was applied and animals were euthanized at different time points…